QTL Mapping and Marker Identification for Sex-Determining: Indicating XY Sex Determination System in the Swimming Crab (Portunus trituberculatus) - Lv, Jianjian; Sun, Dongfang; Huan, Pengpeng; Song, Liu; Liu, Ping; Li, Jian (Frontiers in Genetics, 2018)
Sex determination is an important area of research, which has always had an intriguing aspect in evolutionary and developmental biology. Mapping of sex QTL will be helpful in clarifying the sex determination system. In this study, the sex QTL mapping of Portunus trituberculatus was performed based on a high-density linkage map, and a highly signiﬁcant QTL specifically mapped on a single linkage group was firstly identified (LG24, LOD>14). Twenty markers in the QTL region showed significant associations with sex by association analysis, of which heterogametic genotypes in males supported the XY sex determination mechanism. Two sex-specific markers at the family level were identified via segregation distortion analysis, which were known to be the most closely linked to the sex of P. trituberculatus. Based on sex marker sequences (Marker3840, Marker20320 and Marker10494), three potential sex- related genes were identified, and the qPCR results suggested that these genes were important in spermatogenesis or sex characteristics in males. Our results will contribute to the fine-mapping of sex-determining genes and clarify the sex determination mechanism of P. trituberculatus.